DISCOVERY OF DISTANT OBJECTS BY MEANS OF OPTIC-ELECTRONIC DEVICES, LIKELIHOOD RATIO WHEN THE SIGNAL IS ABSOLUTELY UNKNOWN: DISCOVERY OF DISTANT OBJECTS BY MEANS OF OPTIC-ELECTRONIC DEVICES, LIKELIHOOD RATIO WHEN THE SIGNAL IS ABSOLUTELY UNKNOWN - Stoyanov, Stiliyan; Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The signal registration from distant objects is one of the major problems which concerns many scientists who work in the field of the space physics and the distant methods in the visible and the close infrared part of the optic spectre. For most of the systems which discover distant objects, a very small a priori probability for presence of a signal is characteristic and the a posteriori information becomes proportional to the likelihood ratio. To solve practical problems, the probability relation is conveniently presented by means of dividing the density to the discovery probability.